Empowering career exploration: Designing a vocational interest instrument for junior high school students - Yudhi Satria Restu Artosandi; Sebastianus Widanarto Prijowuntato; Nor Ba’yah Abdul Kadir (Jurnal Penelitian dan Evaluasi Pendidikan, 2025)
Career exploration is a critical developmental task during adolescence; however, many junior high school students lack access to effective tools that accurately identify their vocational interests, thereby limiting informed career decision-making. This study addresses the gap by developing the Vocational Interest Scale, grounded in Holland’s RIASEC model, to support career exploration among junior high school students and establish a standardized framework extendable to senior high and vocational school students for higher education guidance. Employing a research and development methodology, the study encompassed a theoretical review of vocational interest constructs and previous instruments, instrument design with expert evaluations, pilot testing, and psychometric validation. The resultant 24-item scale, which measures the six RIASEC domains—Realistic, Investigative, Artistic, Social, Enterprising, and Conventional—was validated via Confirmatory Factor Analysis using Structural Equation Modeling (LISREL 8.80). Results demonstrated strong factor loadings (0.61–0.89), construct reliability of 0.80, and excellent model fit indices (RMSEA = 0.039), confirming the scale’s validity and reliability. This instrument effectively supports students’ career decision-making based on vocational interests and shows potential generalizability across secondary education levels, thus filling a critical gap in vocational assessment and enhancing career guidance practices for adolescents.